PLANNING DA'WAH MUI DELI SERDANG REGENCY IN OVERCOMING THE PHENOMENON OF PROMISCUITY AMONG YOUTH IN PANTAI LABU DISTRICT - Azhari; Misrah (Al-Mubin, 2025)
The Indonesian Ulema Council (MUI) of Deli Serdang Regency designed a da'wah strategy to overcome the phenomenon of promiscuity among the youth of Pantai Labu District. This approach is carried out in response to the increase in deviant behavior among adolescents which is influenced by a lack of parental supervision and an unconducive environment. The main goal of this program is to foster adolescents to have integrity and strong religious awareness through da'wah coaching. The methods used include collaboration with religious institutions such as BKPRMI, Baznas, as well as the police and village officials. The research method uses a descriptive qualitative approach and data analysis techniques using data collection, reduction and data presentation. In addition, counseling and seminars were carried out on the dangers of drugs, gambling, and promiscuity involving local students. Da'wah safari activities and youth assistance in coastal and minority areas are also part of this program. The results of the study show that this program has a positive impact by increasing adolescents' awareness of religious values and morality. There are still obstacles such as limited funds and lack of support from various parties. In conclusion, MUI Deli Serdang's da'wah planning based on collaboration and community approach has proven to be effective in reducing the number of promiscuity, but needs further support to expand its scope